Effect of Excessive Carrot Juice (Daucus carota) Administration on Uric Acid and Blood Glucose Levels in Rats (Rattus norvegicus) - An, Chau Yu; Kumar, Bhagya Laxmi Ramesh; Gunalan, Jheevanesh; Rajendaran, Harvina; Al Thalhah, Muhammad Rafsa; Hidayatik, Nanik; Novianti, Arindita Niatazya (Journal of Basic Medical Veterinary, 2025)
The consumption of carrot juice (Daucus carota) has been associated with various health benefits, yet its effects on metabolic parameters such as uric acid and blood glucose levels remain inadequately explored. Understanding these effects is crucial for developing dietary recommendations, particularly for conditions related to elevated uric acid and blood glucose. This research aimed to investigate the impact of excessive carrot juice administration on uric acid and blood glucose levels in rats (Rattus norvegicus). The study sought to determine whether carrot juice could serve as a beneficial dietary intervention or if it posed risks for metabolic dysregulation. A true experimental design was employed, utilizing a post-test only control group approach. Four healthy rats were divided into two groups: a control group receiving standard rat feed and a treatment group receiving carrot juice alongside their feed for seven days. Blood samples were collected after a 12-hour fasting period, and uric acid and blood glucose levels were measured using an Easy Touch GCU glucometer. Statistical analysis included descriptive statistics and T-tests to assess significant differences between groups. The results indicated that excessive administration of carrot juice significantly decreased uric acid levels in the treatment group compared to the control group (p < 0.05). Conversely, blood glucose levels were found to be significantly higher in the treatment group (p < 0.05), suggesting a complex interaction between carrot juice consumption and metabolic regulation. The study concludes that while excessive carrot juice can effectively lower uric acid levels in rats, it may also lead to increased blood glucose levels. These findings highlight the need for cautious dietary recommendations regarding carrot juice intake, particularly for individuals at risk of hyperglycemia. Future research should focus on larger sample sizes and explore the effects of carrot juice on various physiological systems and stress-related impacts on metabolic parameters.